The (In)significance of Race in Singapore's Immigration Context: Accounts of Self-Differentiation by Academically Elite Students. Issue 1 (2nd January 2023) - Lu, Luke
ABSTRACT: In order to counter low birthrates, the Singapore state recruits top-performing students from China and Vietnam with scholarships to augment the local talent pool. Another criterion is that most immigrants must be ethnically Chinese, so as to fit into Singapore's majority racial group. This study examines whether and how race (or other factors) might contribute to (dis)affiliation amongst academically elite students in Singapore. Drawing on life history interviews and focus group discussions with top-performing students in Singapore, I investigate how informants engaged in self-differentiation. Instead of race, informants positioned themselves and others along a Singaporean/non-Singaporean polarity, using nationality and time of entry as markers of cultural and structural difference. Chinese linguistic practices were perceived as deficits and impediments to being localised amongst them. The state's assumption—that immigrants can fit in locally just because they fit official racial categories—does not consider how cultural practices are re-valued when transported to a different space.